DP-QPSK Coherent Detection Using 2D Grating Coupled Silicon Based Receiver - Ching-Wei Peng; Chi-Wai Chow; Pin-Cheng Kuo; Guan-Hong Chen; Chien-Hung Yeh; Jyehong Chen; Yinchieh Lai (IEEE Photonics Journal, 2021)
We propose and demonstrate a 100 Gbit/s silicon photonic (SiPh) coherent receiver (Rx) with advanced digital signal processing (DSP) for dual-polarization quadrature-phase-shift-keying (DP-QPSK) transmission. It employs integrated 2D polarization-splitting grating couplers (2D-GCs), modified hybrid mixers and high speed silicon-germanium (SiGe) photodiodes (PDs). The 2D-GC replaced the polarization beam splitters and rotators needed in traditional coherent Rx. Moreover, the SiGe PD has the bandwidth >50 GHz.